Implementation of Agricultural Extension Policy in Rejang Lebong Regency: Implementasi Kebijakan Penyuluhan Pertanian di Kabupaten Rejang Lebong - Nedhi Hermansya; Rahiman Dani; Henny Aprianty (Gayaku Publisher, 2025)
This study aims to analyze the implementation of agricultural extension policy and identify the constraints encountered in its implementation in Rejang Lebong Regency. The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants consisted of the Head of the Agriculture and Fisheries Office of Rejang Lebong Regency, the Coordinator of the Agricultural Extension Center (BPP), Agricultural Extension Workers (PPL), and Farmer Group Leaders. Policy implementation was analyzed using Edward III’s framework, which includes communication, resources, disposition, and bureaucratic structure, while implementation constraints were examined using the framework of Mazmanian and Sabatier. The results indicate that the implementation of the agricultural extension policy in Rejang Lebong Regency has generally been carried out effectively. Communication has been facilitated through continuous dissemination of information and assistance to farmers. Resource support is reflected in the availability of extension workers and supporting facilities, although limitations in personnel and infrastructure remain. The disposition aspect demonstrates a strong commitment among policy implementers, while the bureaucratic structure is supported by implementation guidelines and inter-agency coordination. The main constraints include the complexity of agricultural issues, limited resources, regulatory changes, and farmers’ socio-economic conditions affecting the adoption of agricultural innovations. Therefore, strengthening extension workers’ capacity, improving facilities and infrastructure, and enhancing institutional support are necessary to improve policy implementation effectiveness.